Hazardous to a duke's heart - Jeffries, Sabrina (Lords of hazard, 2025)
"Napoleon's war has ended...Returning to a London he no longer recognizes, and facing astonishing changes in his own family, Lord Jonathan Leighton learns he has inherited a dukedom. But the new nobleman carries the guilt of having wronged his late mentor. Now, he vows to fulfill his promise to find a suitable match for the man's daughter, Victoria... Sharp-witted Victoria would just as soon sculpt the Greek god who has come to take charge of her future. In fact, she has her sights set on founding a school for women artists. As Jonathan matches wits with the talented beauty, revelations from his past--and their connection to her father's demise--threaten to unveil both of their closely held secrets and thrust them into a danger they can only escape together"--